EFEKTIVITAS ANTIHIPERGLIKEMIA TABLET CAMPURAN EKSTRAK DAUN PEPAYA DAN DAUN SALAM PADA TIKUS Sprague dawley - Erni Rustiani; Min Rachminiwati; Lia Suryani (Jurnal Fitofarmaka Indonesia, 2017)
Plants which have a potential effect as antihyperglycemic are papaya leaf and bay leaf. Papaya leaf and bay leaf have a bioactive flavonoid component, which was suggested to have reduction effect on blood glucose. The purpose of this research was to examine the effectiveness of papaya leaf and bay leaf extract, which have been formulated in tablet form to decrease blood glucose level on diabetic Sprague dawley rats induced by alloxan. Twenty male rats were divided into four groups, Each group consists of five rats, namely group I as a positive control (metformin 12.6 mg/200g BW), group II (oral tablet 1.282 mg/200g BW), group III (oral tablet 2.564 mg/200g BW) as extract treatment group, and group IV as negative control. The treatment was carried out for 28 days. The result of this research showed that tablet of papaya leaf and bay leaf extract can be used as antihyperglycemic with the most effective dose was 2.564 mg/200g BB (group III) and the treatment for twelve days.